Deep-sea sedimentary cave structures: geology or fish-made? - Marnor, Camilla M.; Souche, Alban; Hartz, Ebbe H.; Jæger, Maja L.; Schmid, Daniel W. (Frontiers in Marine Science, 2025)
At the Central Mohns Ridge, numerous large cave-like structures were observed in deep-sea sediments at approximately 1200 and 1600 m depth. The glacial eelpout (Lycodes frigidus) was found inhabiting some of these caves, with one individual observed guarding a clutch of eggs. This paper examines the origin of these structures, questioning the hypothesis put forward previously that they are formed by geological processes such as catastrophic fluid vent escapes. No significant disruption of the sedimentary layering was observed, and the caves have a semi-horizontal orientation and are of limited size. We propose that these caves are actively excavated or modified by fish for habitation and protection, a behavior documented in other zoarcids and in other fish families. This observation represents, to our knowledge, the first documented case of parental care by egg guarding inside a cave for L. frigidus.